2018
DOI: 10.17509/ijal.v8i1.11468
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and cultural identity of Indonesian Americans in The United States

Abstract: This article examines the second-generation immigrants in California and focuses on their language use and cultural identity as Indonesian-Americans. This study investigated to what extent home language use and community involvement influenced mastery of Indonesian heritage language and what factors affected the forming of cultural identity. Data were drawn from self-assessed Indonesian Oral Proficiency Questionnaire and in-depth interviews of sixteen Indonesian-Americans aged fifteen to early twenties. Their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The replacement can occur as their adoration of English language is boosted widely through internet-based communication channels. The dominant use of English has, in some ways, affected young people's performances, ways of thinking, and expressing ways of preference (Lie, 2017;Lie, 2018;Lie, Wijaya, & Kuntjara, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement can occur as their adoration of English language is boosted widely through internet-based communication channels. The dominant use of English has, in some ways, affected young people's performances, ways of thinking, and expressing ways of preference (Lie, 2017;Lie, 2018;Lie, Wijaya, & Kuntjara, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Home affects the language spoken by the family members and reflects individual and group self-identity (Lie et al, 2018). Positive home factors like parents' educational level, parents' native language, language environment (through television programs, books, and overseas trips), and language spoken at home, influence students' English learning and acquisition (Rahman, 2015;Dixon et al, 2012;Li, 2007;Norton, 1997) which may inevitably be argued to form self-identity changes (Khatib & Rezaei, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that identity formation can be realized through the use of native language or foreign language. Lie, Wijaya, & Kuntjara (2018) found that language played a central role in the development and expression of identity. They argued that language is the identity markers that can construct speakers' social identity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%